Burden and risk factors for gallbladder and biliary tract diseases in China from 1990 to 2021 and burden predictions of risk factors for the next 15 years - Zhao, Shijun; Zhou, Yan; Tang, Wangyou; Zhao, Cheng; Wang, Lang; Zhu, Xianglin; Liang, Hao; Zhang, Jie; Gao, Tian; Ding, Yinlu (Frontiers in Medicine, 2025)
BackgroundGallbladder and biliary tract diseases (GBDT) is a common digestive disorder; however, comprehensive epidemiological data from China are still limited.MethodsThis study utilized the Global Burden of Disease Study 2021 database to examine the burden of GBDT from 1990 to 2021. The key metrics analyzed included age-standardized incidence rate (ASIR), prevalence rate (ASPR), rate of mortality (ASMR), and age-standardized disability-adjusted life years rate (ASDR). Furthermore, the study analyzed trends and future projections concerning GBDT linked to high body mass index (HBMI). Joinpoint regression analyses were performed to evaluate trends in disease burden from 1990 to 2021. Furthermore, the study analyzed trends in mortality and DALYs attributable to GBDT linked to high HBMI and made projections for HBMI-related GBDT mortality and disability-adjusted life years (DALYs) over the next 15 years.ResultsFrom 1990 to 2021, the ASPR and ASIR of GBDT in China showed fluctuating trends, and the ASPR and ASIR of GBDT in globally also fluctuated similarly, but with a smaller amplitude, and the overall trend showed a decreasing trend. The ASMR showed a lower level with a stable trend, and the ASDR also showed a lower level but slowly decreased annually. The incidence, prevalence, mortality and DALYs of GBDT were correlated with old age and female. The burden of disease attributable to GBDT due to HBMI was concentrated in the very old. The BAPC model predicts an increase in the DALYs and a decrease in mortality, deaths, and DALYs rate for GBDT attributable to HBMI over the next 15 years.ConclusionGBDT remains a major global public health problem, and the development trend of GBDT in China has far-reaching global implications. In China, the number of incident cases of GBDT and ASIR increased between 1990 and 2021, and GBDT, due to HBMI, poses a greater disease burden in China, both in the past and in the future.